Gerassi, ventriloquist of Sartre. Reading of Talking with Sartre by John Gerassi (Nóema, 2013)
A critical review of J. Gerassi’s book, Talking with Sartre, Yale University Press, 2009.
Keywords: Sartre; Existentialism; Beauvoir; John Gerassi